1999
DOI: 10.1046/j.1463-1318.1999.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trimetazidine in ethanol‐ and acetic acid‐induced colitis: oxidant/anti‐oxidant status

Abstract: There is overwhelming evidence in favour of a significant role of reactive oxygen metabolites (ROM) in the pathophysiology of inflammatory bowel disease (IBD) in man and in experimental animal models. This study was undertaken to investigate the possible protective effects of pretreatment with trimetazidine (TMZ) on the oxidant-anti-oxidant balance in ethanol- and acetic acid-induced colonic damage in rats. TMZ was chosen because of its various cytoprotective features (preserving cellular ATP levels, limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As a result, TMZ has improved the histopathologic damage and in addition decreased tissue hydroxyproline content. In previous studies, the protective effect of TMZ has been demonstrated in various experimental damage models of the gastrointestinal system in rats [22,23]. Girgin et al [22] have shown that TMZ contributed significantly to the preservation of the antioxidant pool via conservation of intracellular glutathione levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, TMZ has improved the histopathologic damage and in addition decreased tissue hydroxyproline content. In previous studies, the protective effect of TMZ has been demonstrated in various experimental damage models of the gastrointestinal system in rats [22,23]. Girgin et al [22] have shown that TMZ contributed significantly to the preservation of the antioxidant pool via conservation of intracellular glutathione levels.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the protective effect of TMZ has been demonstrated in various experimental damage models of the gastrointestinal system in rats [22,23]. Girgin et al [22] have shown that TMZ contributed significantly to the preservation of the antioxidant pool via conservation of intracellular glutathione levels. Trimetazidine protected the histological appearance of the pancreas and considerably reduced malondialdehyde concentration in acute pancreatitis model in rats, indicating that the beneficial effect was achieved by the elimination of free oxygen radicals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the infiltration of leukocytes, monocytes, and neutrophils during inflammation can further enhance intestinal ROS production through both respiratory burst enzymes and prostaglandin and leukotriene metabolism (Babbs, 1992 ). Several studies have demonstrated increased ROS/RNS levels within the intestinal epithelium of patients with IBD (Kruidenier and Verspaget, 2002 ; Pravda, 2005 ; Rezaie et al, 2007 ) and in murine models of experimental colitis (Girgin et al, 1999 ; Tham et al, 2002 ; Narushima et al, 2003 ; Sundaram et al, 2003 ; Oz et al, 2005 ; Siddiqui et al, 2006 ; dos Reis et al, 2009 ; Kajiya et al, 2009 ; Abdolghaffari et al, 2010 ; Yao et al, 2010 ; Lenoir et al, 2011 ; Ock et al, 2011 ; Sengül et al, 2011 ; Borrelli et al, 2013 ; Arab et al, 2014 ). High concentrations of oxidized molecules have also been measured in the plasma, serum, exhaled air, and saliva of patients with IBD (Tüzün et al, 2002 ; Rezaie et al, 2006 ).…”
Section: Mitochondrial Dysfunction In Ibdmentioning
confidence: 99%
“…Rats were initially weighed and randomized into three groups ( n = 10); control, silica and silica‐TMZ in which silica or saline were intranasally instilled on Day 1, and oral treatments with either TMZ (7 mg/kg/day, [ 26,27 ] silica‐TMZ group) or the vehicle for TMZ (0.5% CMC, 10 ml/kg/day, both control group and silica group) were administered orally for 60 days. Of note, shorter‐term studies (7 days) were used to test the beneficial effects on the inflammatory rather than the fibrotic phase that follows exposure to silica.…”
Section: Methodsmentioning
confidence: 99%